Numerical modelling of multiphase flow, heat flow and pollutant transport in deforming porous media for subsurface systems - Abd. Rahman, Norhan; Mohd. Kassim, Amir Hashim (Universiti Teknologi Malaysia, 2000)
Groundwater plays an important role in the development of the world water resources potential. Groundwater has to be protected from the increasing threat of subsurface contamination. Subsurface contamination can be caused by leakage from ponds and lagoons which are widely used as components of larger waste-disposal systems, pesticides from agricultural soils, industrial product leaking underground storage tanks and pipelines and surface spills. Until today. groundwater contamination becomes most popular aspects to discuss. The migration of NAPLs, process of dissolution, factor influences. effects and the techniques for remediation of groundwater contaminant was done in order to make sure that this source could be use in long terms. Due to these reasons. needed some alternative in order to simulate the groundwater system to get the results of the contaminant. Many researchers were involved to develop a model of groundwater contamination by numerical method. The simulation of groundwater contamination by NAPLs such as organic solvent, petroleum hydrocarbon requires a solution of the multiphase flow equation in deforming porous medium. The multiphase flow namely gas, water and NAPL was developed for a fully coupled numerical model for subsurface system by Ralunan (1998). . Many of this pollutant are slightly such water soluble and highly volatile fluids, which it may exist as non-aqueous phase liquid (NAPL). The remaining non-aqueous phase liquids may persist for long periods of time, slowly dissolving into the groundwater and moving in the water phase through advection and dispersion. A study of numerical modelling of multiphase flow, heat flow and pollutant transports are very important to describe the phenomena of contamination in soil especially by organic waste such as Dense Non-aqueous Phase Liquid (DNA-PL). A numerical model needed in order to study the movement of organic pollutants in subsurface system. This simulation also developed for use in non-isothermal problems of gas migration landfill system and for organic vapor in unsaturated zone. In additional a fully coupled model of water flow and airflow incorporate pollutant transport in deformable porous media has been studied by Schrefler (1995) which does not consider the interphase mass transfer in the simulation model. Furthermore, transport contaminant may cause by organic liquid where the density of the gas in contact with the liquid changed with respect to the ambient of soil gas. Simulating the transport of volatile organic compound may show the importance of including density-driven gas flow as a transport mechanism in the unsaturated zone. In contaminant gas migration, the overall porosity, air and water saturation level effects the rates of diffusion in porous media. The equations using are such water phase tortuosity (ti) , Henry's law, Galerkin Method and others. The simulating are performed for volatile organic compound and the physical properties of the model.